A Review of the Quantitative Research on Multigrade Instruction - Bruce A. Miller (Journal of Research in Rural Education, 1990)
This paper examines the quantitative research literature regarding the effects multigrade classroom organization has on student cognitive and affective outcomes. Findings indicate that student achievement is neither better nor worse in multigrade classrooms. However, areas relating to student affect significantly favor the multigrade environments. But quantitative studies only reveal one dimension of multigrade instruction. Research is needed that provides a rich, detailed description of multigrade classroom life in, especially high performing classrooms